A note on the optimal speed of transition: Aghion and Blanchard revisited - Eric Nævdal; Martin Wagner (German Economic Review (GER), 2025)
This note illustrates, by reconsidering the seminal optimal speed-of-transition model of Aghion, P., and O. J. Blanchard. (1994. "On the Speed of Transition in Central Europe." NBER Macroeconomics Annual 9: 283-319), that optimal transition paths, in general, exhibit nonlinearities and discontinuities. Aghion and Blanchard consider only an approximate solution with a constant unemployment rate over the transition process. The exact solution features an increasing unemployment rate with a discontinuity when the state sector is closed down at the optimally chosen endpoint of transition. Economic transition problems bear many similarities to scrap value problems with free terminal time, often encountered in resource economics. In relation to the transition to a green economy, the discussion in this note therefore casts doubt on the optimality of a green transition discussed in, e.g., the European Union in terms of politically specified rather than optimally designed milestones for emissions reductions, i.e., by -55% compared to 1990 levels until 2030 and net zero until 2050.
Keywords: C61; E61; P20; 330; dynamic optimization; end-of-transition; optimal unemployment rate; transition